Integrating Ki Hajar Dewantara's Philosophical Values and Islamic Legal Principles in the Hudoq Kita Dance Tradition - Tri Indrahastuti; Indar Sabri; Setyo Yanuartuti; Arif Hidajad; Syaiful Arifin (Madania: Jurnal Kajian Keislaman, 2025)
This study examines the integration of Ki Hajar Dewantara's philosophical values with Islamic legal principles within the Hudoq Kita dance tradition of East Kalimantan. Using a qualitative–descriptive approach supported by a literature review of Dewantara's educational thought and Islamic legal theory, this research develops a conceptual framework that connects moral, cultural, and spiritual values embodied in the Hudoq Kita dance. Ki Hajar Dewantara's triadic principles—ing ngarsa sung tuladha (leading by example), ing madya mangun karsa (inspiring initiative), and tut wuri handayani (empowering from behind)—serve as a pedagogical basis for character formation and cultural learning. These principles closely align with foundational concepts in Islamic law, such as maslahah (public benefit), ʿadl (justice), and wasatiyyah (moderation), which emphasise ethical balance, social responsibility, and communal well-being. The relevance of these values becomes evident in the Hudoq Kita dance, a ritual Dayak tradition performed as an expression of gratitude, supplication, and respect for nature. It’s symbolic masks, rhythmic movements, and collective performance illustrate the harmony of feeling, thought, and will (olah rasa, olah pikir, olah karsa) emphasized by Dewantara. The findings indicate that the Hudoq Kita dance functions not only as an artistic and cultural expression but also as an educational medium for internalizing moral and spiritual values consistent with Islamic ethical teachings. Through its ritual symbolism and environmental reverence, the Hudoq Kita dance cultivates sincerity, cooperation, humility, and respect for God's creation—virtues that resonate with the maqâṣid al-syarîʿah in safeguarding life, intellect, and ecological harmony. Penelitian ini mengkaji integrasi nilai-nilai filosofis Ki Hajar Dewantara dengan prinsip-prinsip hukum Islam dalam tradisi Tari Hudoq Kita di Kalimantan Timur. Menggunakan pendekatan kualitatif–deskriptif yang didukung oleh telaah literatur terhadap pemikiran pendidikan Ki Hajar Dewantara dan teori hukum Islam, penelitian ini mengembangkan kerangka konseptual yang menghubungkan nilai moral, kultural, dan spiritual yang terwujud dalam Tari Hudoq Kita. Tiga prinsip utama Ki Hajar Dewantara—ing ngarsa sung tuladha (memberi teladan), ing madya mangun karsa (membangkitkan semangat dan inisiatif), dan tut wuri handayani (memberi dorongan dari belakang)—menjadi dasar pedagogis bagi pembentukan karakter dan pembelajaran budaya. Prinsip-prinsip ini selaras dengan konsep dasar dalam hukum Islam seperti maṣlaḥah (kemaslahatan), ʿadl (keadilan), dan wasatiyyah (moderasi), yang menekankan keseimbangan etis, tanggung jawab sosial, dan kesejahteraan bersama. Relevansi nilai-nilai tersebut tampak jelas dalam Tari Hudoq Kita, tradisi ritual Dayak yang dipentaskan sebagai ungkapan syukur, permohonan, dan penghormatan terhadap alam. Topeng-topeng simbolik, gerak ritmis, serta performa kolektif dalam tarian ini mencerminkan harmoni antara rasa, pikir, dan kehendak (olah rasa, olah pikir, olah karsa) sebagaimana ditekankan oleh Dewantara. Temuan penelitian menunjukkan bahwa Tari Hudoq Kita tidak hanya berfungsi sebagai ekspresi seni dan budaya, tetapi juga sebagai media pendidikan untuk menginternalisasikan nilai-nilai moral dan spiritual yang sejalan dengan etika Islam. Melalui simbolisme ritual dan penghormatan terhadap lingkungan, Tari Hudoq Kita menumbuhkan keikhlasan, kerja sama, kerendahan hati, serta penghormatan terhadap ciptaan Tuhan—kebajikan yang selaras dengan maqâṣid al-syarîʿah dalam menjaga kehidupan, akal, dan keharmonisan ekologis.